Dampak Program Keluarga Harapan (PKH) terhadap Kesejahteraan Keluarga di Desa Padang Seurahet Kecamatan Johan Pahlawan Kabupaten Aceh Barat - Lia Muliana; Mursyidin Mursyidin; Muharriyanti Siregar (Universitas Teuku Umar, 2021)
The Family Hope Program (PKH) is a conditional cash transfer program for low-income families. The requirement is to be actively involved in education and health. The Family Hope Program in Indonesia was implemented in 2007 to alleviate poverty and prosper low-income families. The research and writing of this journal aim to determine the impact of PKH on family welfare and see if there is a reduction in poverty after the government realizes the Family Hope Program. This study uses a qualitative method with a descriptive approach. The study results indicate that the impact of PKH on beneficiary families, including the cash provided, can meet consumption or family needs and help the economy of PKH recipient families. The implementation of the program can reduce poverty in Aceh. The percentage of the poverty rate fell to 0.02%. The limitation of the research is the impact of PKH on family welfare and wants to examine whether there is a decrease in the percentage of poverty in Aceh or Aceh Barat. The practical implication of this research is to provide information to the government that PKH can improve the welfare of low-income families. The social significance is to give the government and the general public that the implementation of social assistance programs, one of which is the Family Hope Program, can reduce poverty rates in Aceh or West Aceh. The originality of the research is supported by previous research related to the author’s research study.